Pengaruh Faktor Internal terhadap Profitabilitas dengan NPF sebagai Variabel Intervening Pada Bank Umum Syariah di Indonesia Periode 2015-2020 - Ajeng Putri Nurfadila; Endang Hatma Juniwati; Banter Laksana (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study aims to determine the magnitude of the effect of the variables CAR, FDR and BOPO as an independent variable directly on ROA as the dependent variable and indirectly through the intervening variable, namely NPF at Islamic Commercial Banks in Indonesia for the 2015-2020 period. The data used is secondary data derived from the Statistik Perbankan Syariah OJK. The method used in this research is descriptive research with a quantitative approach using Path Analysis and supported by SPSS 25 software as a data processing application. The results showed that CAR have a negative and significant effect and BOPO have a positive and significant effect on NPF, while FDR have no significant effect on NPF. Furthermore, BOPO has a negative and significant effect on ROA, while CAR, FDR and NPF have no significant effect on ROA. The NPF cannot mediate the effect of CAR, FDR and BOPO on ROA.